2011
DOI: 10.1007/s00384-011-1241-5
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of clinical course and the analysis of the frequency of the inflammation and dysplasia in the intestinal J-pouch at the patients after restorative proctocolectomy due to FAP

Abstract: PurposeThe main operative method in familial adenomatous polyposis (FAP) patients is restorative proctocolectomy with “J”-shaped pouch and temporary loop ileostomy. The aim of the study was the analysis of the frequency of the dysplasia and inflammation in the intestinal pouch and prognosis of the clinical course in FAP patients after restorative proctocolectomy.MethodsA group of 165 FAP patients (86 females and 79 males, mean age 22.49 ± 12) subjected to a restorative proctocolectomy in the years 1985–2009 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
1
19
1
1
Order By: Relevance
“…Pouchitis is a high‐incidence complication after IPAA, and approximately half of all patients with inflammatory bowel disease suffer from pouchitis; however, the incidence of pouchitis is much lower in patients with hereditary CRC than in those with inflammatory bowel disease . The pouchitis rate in this study was not much lower than the rates reported in studies on hereditary CRC; nonetheless, the rate in this study was lower than the rates reported in studies on ulcerative colitis, which may be a reflection of the surgical technique and the particularities of ulcerative colitis.…”
Section: Discussioncontrasting
confidence: 69%
“…Pouchitis is a high‐incidence complication after IPAA, and approximately half of all patients with inflammatory bowel disease suffer from pouchitis; however, the incidence of pouchitis is much lower in patients with hereditary CRC than in those with inflammatory bowel disease . The pouchitis rate in this study was not much lower than the rates reported in studies on hereditary CRC; nonetheless, the rate in this study was lower than the rates reported in studies on ulcerative colitis, which may be a reflection of the surgical technique and the particularities of ulcerative colitis.…”
Section: Discussioncontrasting
confidence: 69%
“…The incidence of pouchitis in FAP patients varies widely in literature from about 5 % [52] to more than 20 % [53], and the definition of pouchitis is controversial. Furthermore, pouchitis is normally dealt with by general practitioners, so therefore data regarding the incidence of pouchitis in this series has not systematically been documented.…”
Section: Discussionmentioning
confidence: 99%
“…FAP patients are also at risk for extracolonic manifestations including gastric and duodenual polyps, osteomas and dental anomalies, congenital hypertrophy of the retinal pigment epithelium, desmoids and other soft tissue tumors. The current standard of treatment includes intensive monitoring with prophylactic surgery (either restorative proctocolectomy or ileorectal anastomosis [IRA]) when the adenoma burden becomes unmanageable by endoscopy, often by 20 years of age [20,21]. While surgery is life-saving [22], reported postoperative quality-of-life outcomes are highly variable [23–26] and suggest that surgery may increase the risk of infertility [27,28].…”
Section: Familial Adenomatous Polyposismentioning
confidence: 99%